Violencia Intrafamiliar y Rendimiento Académico en Escolares, Huamachuco 2018 - Benites Segura, Rosely (2019)
The present descriptive, correlational research study, of cross section, was carried out at the "San Nicolás" Public Educational Institution of the District of Huamachuco, Sánchez Carrión Province, La Libertad Department, whose general objective was to determine how intrafamily violence influences the academic performance of students; A sample consisting of 102 children was considered, the Epi-Info software version 7.2.0.1 was used to calculate the sample size and this will consist of 3 classrooms of the 5th grade, who met the following inclusion criteria: Chronological age between 9 and 11 years old, who are enrolled and have regular attendance at the School, who voluntarily accepted to participate in the study and who do not have problems of mental alteration. For data collection, a survey was applied to identify intrafamily violence, and to register academic performance, the record of the first two bimesters was used. The results obtained were that 52 porcent of the children presented intrafamily violence, and 48 porcent did not present. Of the students that present intrafamily violence, the highest percentage of academic performance is in the process and expected accomplishment, and those who do not show violence, the highest percentage of academic performance is in the expected accomplishment.